Correlation Between Fear of Missing Out and Internet Addiction in Students - Yara Andita Anastasya; Cut Meurah Hadiah; Ika Amalia; Ella Suzanna (International Journal of Islamic Educational Psychology, 2022)
Nowadays, technological advances continue to develop every year. The existence of technology makes it easy for everyone to access the internet anywhere and anytime; everyone can also use the internet at many sources, such as online games, chatting, YouTube, and many others. This research involved business administration students. The significance value (2 tailed) found was 0.000, 0.05, so there was a significant relationship between the fear of missing out (FoMO) variable and internet addiction. In addition, there was a positive correlation and a contribution between FoMO and internet addiction in business administration students with a significance of 0.000 0.05. It signifies that if FoMO increases, internet addiction will also increase. The contribution of internet addiction to the FoMO was 52.8%. The accepted hypothesis in this study revealed that FoMO is one of the factors influencing internet addiction in business administration students.